The Effect of Brand Image on Customer Loyalty, Customer Satisfaction as a Mediator: An applied study on a sample of Asiacell customers - Dhadjer, Ammar Youssef (Finance and Business Economies Review, 2020)
This study aims to provide a conceptual framework of brand image , customer satisfaction and customer brand loyalty. This study sheds light on the importance of brand image and its effect on customer brand loyalty through the mediation role of customer satisfaction by conducting an applied study on a sample from Asiacell customers. The study uses a questionnaire which has been developed for the study aim. It has been arrived in this study to a number of results and suggestions which indicate to the positive effect of the brand image on customer satisfaction and customer brand loyalty. Also, customer satisfaction plays as a mediator in the relationship between brand image and customer brand loyalty. The study provides directions for future studies that are related to the study’s subject.